Improving Pediatrician's Behavioral Health Competencies Through the Project ECHO Teleconsultation Model. (October 2020) - Hostutler, Cody A.; Valleru, Jahnavi; Maciejewski, Heather M.; Hess, Amy; Gleeson, Sean P.; Ramtekkar, Ujjwal P.
Project ECHO (Extension for Community Healthcare Outcomes) is a teleconsultation model for enhancing the treatment of underserved patients in primary care. Previous behavioral health (BH) adaptations of Project ECHO have primarily focused on adults or specific diagnoses and have relied on self-reported outcomes. The purpose of this pilot was to adapt Project ECHO to support pediatric primary care providers in addressing common BH needs and to conduct an initial evaluation of its effectiveness. Overall, participants reported high levels of satisfaction and a statistically significant improvement in their overall knowledge and skills ( P = 0.001). Participation was also associated with a reduction in the use of psychotropic polypharmacy. This pilot adds to a growing body of literature suggesting that Project ECHO is a promising workforce development approach to build competencies for the management of BH issues in primary care.